THE CULTURAL SHIFT OF THE POEM “DIORAMA” BY SOSIAWAN LEAK: THE STUDY OF VAN DIJK's CRITICAL DISCOURSE ANALYSIS: PERGESERAN KULTURAL PUISI “DIORAMA” KARYA SOSIAWAN LEAK: KAJIAN ANALISIS WACANA KRITIS VAN DIJK - Adhetia Sukmafitriani Sugianto; Rustono Rustono; Benardus Wahyudi Joko Santoso (Jurnal Kata, 2022)
This study aims to reveal the meaning of cultural shift in the poem "Diorama" by Sosiawan Leak. The theory used for cultural shift is Van Dijk's critical discourse analysis model. This research has a descriptive qualitative design with a theoretical approach to Van Dijk's critical discourse analysis model. The source of research data is the poem "Diorama" by Sosiawan Leak. Van Dijk's critical discourse analysis consists of an analysis of the structure in the text, cognition, and the social context that surrounds the discourse. The data collection technique uses reading techniques in the form of heuristics related to linguistics or language conventions based on interpreter findings, while hermeneutics is based on readings made to interpret the "Diorama" poem based on the scalpel used. The data analysis technique used is content analysis, with the technique of presenting research results based on the discourse analysis of the Teun A. Van Dijk model. The results show that the poem "Diorama" reflects various forms of resistance and criticism of the colonization of the media crew in an effort to reveal oppression, violence, injustice, alienation, and education that is not intellectual.